Pengaruh Gaya Kepemimpinan Kepala Sekolah dan Kepuasan Kerja Guru Terhadap Kinerja Guru Sekolah Dasar Negeri Sekecamatan Kertapati - Indah Ardianti; Tri Widayatsih; Pahlawan Pahlawan; Hairani Hairani; Ika Lestari (CV. ULIL ALBAB CORP, 2024)
The aim of this research is to determine and analyze the influence of the principal's leadership style and teacher job satisfaction on teacher performance in State Elementary Schools in the Kertapati District. The sample in this research was 105 students of government schools in kertapati sub-district. The data collection method used in this research is a questionnaire with a Likert scale. The results of this research show that leadership style has an influence on the performance of teachers in Kertapati District. This is shown by the correlation coefficient (r) value of 0.861, meaning that it can be interpreted that the leadership style variable has a very strong relationship to improving teacher performance variables in Kertapati District. R2 is 0.864, which means that the leadership style variable is able to explain 86.4% of the work performance variable, while 15.6% is explained by other factors not explained in this research. Job satisfaction has a significant effect on the performance of teachers in Kertapati District, which is shown by the correlation coefficient (r) value of 0.849, meaning that it can be interpreted that the job satisfaction variable has a very strong relationship to improving teacher performance variables in Kertapati District. R2 is 0.864, which means that the job satisfaction variable is able to explain 86.4% of the work performance variable, while 15.6% is explained by other factors not explained in this research. Leadership style and job satisfaction have a positive and significant effect on the performance of teachers in Kertapati District, which is shown by the correlation coefficient (r) value of 0.951, meaning that it can be interpreted that the variables of leadership style and job satisfaction have a very strong relationship to improve teacher performance variables. in Kertapati District. R2 is 0.904, which means that the leadership style and job satisfaction variables are able to explain 90.4% of the work performance variable, while 9.6% is explained by other factors not explained in this research. For this reason, it is recommended that the principal be able to protect and set a good example for teachers. Applying a good leadership style will motivate teachers to produce good ways of working too. Teachers are able to express complaints regarding the principal's leadership style and the feedback they receive from the work they have done.